An 88-year-old woman with acute disseminated encephalomyelitis following messenger ribonucleic acid-based COVID-19 vaccination - Mai Shimizu (Elsevier, 2021)
A global pandemic has resulted from the emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19). To control the spread of SARS-CoV-2 infection, several SARS-CoV-2 vaccines have been developed and administered in a wide range of age groups. Messenger ribonucleic acid (mRNA)-based COVID-19 vaccines are the most widely used. We present the case of an 88-year-old woman who was diagnosed with acute disseminated encephalomyelitis (ADEM) following her second mRNA COVID-19 vaccination. She was admitted to hospital with disturbed consciousness (Glasgow Coma Scale E1V1M4) and gaze-evoked nystagmus. Brain magnetic resonance imaging revealed bilateral presence of middle cerebellar peduncle sign. Following steroid pulse therapy, clinical symptoms improved. The occurrence of ADEM following COVID-19 vaccination does not question the importance of vaccination programs during the COVID-19 pandemic. COVID-19 vaccines have been administered to individuals of a wide range of ages, from children to older adults. Thus, ADEM could occur following COVID-19 vaccination at any age, although ADEM is rare in older adults.